„Językowy telemost” jako nowa forma kształcenia kompetencji interkulturowej i doskonalenia warsztatu nauczyciela języka obcego - Wojakowska, Marta; Sosnowski, Wojciech (Neofilolog, 2023)
The shift to distance learning in foreign languages teaching has further emphasized the need for communication and interaction set in a context close to authentic experience. The starting point of the research was the assumption that a new classroom practice developed during the pandemic –the “language space bridge” – contributes to the development of language education and influences the improvement of intercultural competence. This article is based on a study of the “language space bridge”, a non-institutional educational platform running between 2020 and 2022 and set up by an international team of foreign language teachers collaborating under an Erasmus+ project. The article discusses theoretical aspects of intercultural communication and forms of training. A description of the research process is followed by the presentation of the didactic process itself. Having conducted an in-depth analysis of the evaluation questionnaires completed by the students and teachers, the authors conclude that the new educational platform might be a way to improve intercultural competence for both students and teachers.